Skin renewal activity of non-thermal plasma through the activation of β-catenin in keratinocytes - J. H. Choi (Nature Portfolio, 2017)
Abstract For recent years, devices that generate non-thermal plasma (NTP) have been introduced into the field of dermatology. Since NTP has demonstrated strong anti-pathogenic activity with safety of use, NTP was first applied to sterilize the skin surface to aid in the healing of various kinds of skin diseases. However, the effect of NTP on skin regeneration has not yet been fully explored. In this study, the effect of NTP on the growth of keratinocytes was tested using the HaCaT human keratinocyte cell line and HRM2 hairless mice. Treatment with NTP allowed confluent keratinocytes to escape from G1 cell cycle arrest and increased the proportion of cells in S and G2 phases. In particular, NTP treatment immediately dispersed E-cadherin-mediated cell-to-cell interactions, resulting in the translocation of β-catenin to the nucleus and leading to the enhanced transcription of target genes including c-MYC and cyclin D1. Moreover, repeated treatment of the mice with NTP also stimulated epidermal expansion by activating β-catenin in the epidermal cells. The symptoms of cellular DNA damage were not detected after NTP treatment. Taken together, these results demonstrate that NTP may be employed as a new type of skin regenerating device.